Introverted and yet effective? A faceted approach to the relationship between leadership and extraversion - Liegl, Simon; Furtner, Marco R. (Frontiers in Psychology, 2023)
Extraversion and its facets of assertiveness and sociability were identified as stable predictors for leader emergence and effectiveness. However, recent research suggested that extraversion may lie in the eyes of the beholder; it might not be the leader’s possession but their followers’ attribution of the trait that shapes these criteria of leader success. In our study, we reverse-engineered this relationship and assessed the effects of effective leadership behaviors on personality perceptions. More specifically, we created scenarios of a leader responding to coordination challenges with passive-avoidant, transactional, or transformational leadership behaviors. We presented 204 participants with these scenarios and assessed how extraverted, assertive, and sociable they perceived the leader to be. Interestingly, and not fully meeting our expectations, these ascriptions of traits did not directly relate to the effectiveness of the behaviors, as the moderately effective transactional leadership style garnered the highest ascriptions of extraversion and its facets. Further, ascriptions of extraversion to the transformational behavior of intellectual stimulation were remarkably low, matched only by the laissez-faire dimension of the passive-avoidant leadership style. These unexpected, yet explainable findings shed light on potential associations between introversion and empowering leadership practices and provide a great potential for further discourse.